Needs analysis of interactive physics e-modules in Senior High School to develop students’ higher-order thinking skills and self-regulated learning - Fian Rifqi Irsalina; Lina Aviyanti; Mimin Iryanti (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2025)
This study examines the critical role of interactive e-modules in enhancing physics learning in senior high schools by identifying the pedagogical and technical needs of both students and teachers. A descriptive survey design employing a mixed-methods approach was used, integrating quantitative data from student questionnaires with qualitative insights obtained through teacher interviews. The participants consisted of 46 Grade XI students from a senior high school in Nganjuk and eight physics teachers who actively integrate technology into their instructional practices. Data were analyzed using descriptive statistics and thematic analysis. The findings indicate a clear need for innovative instructional media. Although 52% of students reported an interest in physics, 48% reported difficulties understanding key concepts, highlighting the need for more accessible, interactive learning approaches. Notably, 85% of students preferred digital learning media, such as e-modules and instructional videos, over traditional textbooks, and 61% reported using digital devices daily for learning. Most students perceived e-modules as beneficial, particularly valuing features that provide clearer explanations and interactive elements, including animations and videos. Teachers corroborated the effectiveness of e-modules in facilitating the comprehension of abstract physics concepts but emphasized the need for systematic training and improved technical infrastructure to ensure effective implementation. In conclusion, the development of interactive e-modules is essential for enhancing student engagement, fostering higher-order thinking skills (HOTS), and promoting self-regulated learning (SRL). Therefore, this study recommends that educational institutions prioritize targeted teacher-training programs and infrastructure development to support the optimal and sustainable integration of e-modules into physics education.